Transradial Approach for Percutaneous Interventions - Zhou, Yujie; Kiemeneij, Ferdinand; Saito, Shigeru; Liu, Wei.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2017)
This book outlines the state of the art in transradial intervention and illustrates case-based learning for the transradial access (TR access) technique, especially in complex lesions. Offering a practical guide, it includes essential tips and tricks on how to overcome anatomical complexities, how to avoid radial complications, multiple case-based learning for very complex PCI, etc. It also discusses the advantages of the TR intervention, such as reduced vascular access site complications and immediate patient mobilization. The authors, who work at respected transradial centers, share their extensive experience with TR intervention, providing a comprehensive review of current percutaneous interventions for cardiac surgeons and cardiothoracic surgical residents. Editor Yujie Zhou is a Professor at the department of Cardiology, Anzhen Hospital, Beijing, China. Editor Wei Liu is a physician at the same department. Editor Ferdinand Kiemeneij is is interventional cardiologist at Department of Cardiology, Tergooi Hospital, Blaricum, the Netherlands. Editor Shigeru Saito, FACC, FSCAI, FJCC, is the director of cardiology and Catheterization Laboratories, Shonan Kamakura General Hospital, Kamakura, Japan.
History and current perspective of transradial intervention -- Transradial and transfemoral intervention -- Transradial puncture -- Complications of transradial procedures -- Basic of transradial intervention -- Transradial PCI for Complex lesions -- Transradial approach for STEMI -- Transradial approach for calcified and tortuous lesions -- Transradial approach for left main lesions -- Transradial approach for bifurcation lesions -- Transradial approach for Chronic total occlusion -- Transradial approach for prior CABG artery -- Circulatory support in transradial intervention -- Transradial intervention with supporting device -- Transradial approach for peripheral artery disease -- Transradial approach for Carotid stenting -- Transradial approach for structural heart disease -- Transradial approach for Radial denervation.
Keywords: Medicine; Angiology; Cardiology; Cardiac surgery; Medicine & Public Health; Cardiology; Angiology; Cardiac surgery